2021
DOI: 10.3390/md19010040
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Tetrodotoxins in the Cotylean Flatworm Prosthiostomum trilineatum

Abstract: Several polyclad flatworm species are known to contain high levels of tetrodotoxin (TTX), but currently TTX-bearing flatworms seem to be restricted to specific Planocera lineages belonging to the suborder Acotylea. During our ongoing study of flatworm toxins, high concentrations of TTXs were detected for the first time in the flatworm Prosthiostomum trilineatum, suborder Cotylea, from the coastal area of Hayama, Kanagawa, Japan. Toxin levels were investigated by high performance liquid chromatography-tandem ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…LC-MS experiments were performed on a Shimadzu LC-20AD solvent delivery system and a SCIEX X500R Q-TOF Mass Spectrometer with an ESI ion source. The filtered solution was subjected to LC-MS/MS analysis with multiple reaction monitoring (MRM) using an Atlantis HILIC Silica column (Waters, Milford, MA, USA) with gradient elution, following the method used in a previous study [28]. The optimized transitions for TTX were m/z 320 > 302 for qualification and m/z 320 > 162 for quantification, and those for 5,6,11-trideoxyTTX were m/z 272 > 254 and m/z 272 > 162.…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…LC-MS experiments were performed on a Shimadzu LC-20AD solvent delivery system and a SCIEX X500R Q-TOF Mass Spectrometer with an ESI ion source. The filtered solution was subjected to LC-MS/MS analysis with multiple reaction monitoring (MRM) using an Atlantis HILIC Silica column (Waters, Milford, MA, USA) with gradient elution, following the method used in a previous study [28]. The optimized transitions for TTX were m/z 320 > 302 for qualification and m/z 320 > 162 for quantification, and those for 5,6,11-trideoxyTTX were m/z 272 > 254 and m/z 272 > 162.…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…These TTX-bearing flatworms have been found to harbor TTX and 5,6,11-trideoxy-TTX, which was comparable to the amount of TTX [28,29]. When TTX-bearing fish acquire the toxin from their prey, it would be expected that they would ingest it and its related compounds directly from their prey, and that the compositional ratios in the prey would be reflected in that of the predators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 40 years, TTX was found in extracts of the marine flatworms Planocera multitentaculata [159,160] and Planocera reticulata (type A) [161,162]. Subsequent studies showed the presence of TTX in several marine [125,163,164] and terrestrial [165] flatworms. In P. multitentaculata, the most toxic organs are the oviducts filled with mature eggs and organs of the digestive (including the pharynx) and reproductive systems; a weak neurotoxic effect of the mucus enveloping the worm was observed [160,166].…”
Section: Platyhelminthesmentioning
confidence: 99%
“…The copyright holder for this this version posted September 19, 2021. ; https://doi.org/10.1101/2021.09.16.460554 doi: bioRxiv preprint Because it has been reported that TTX-bearing prey organisms, such as bivalves and gastropods (Biessy et al, 2019), ribbon worms (Cephalothrix cf. simula; Vlasenko and Magarlamov, 2020), and flatworm (Prosthiostomum trilineatum; Suo et al,2021) have 5,6,11-trideoxyTTX as well as TTX. Green spotted puffer feed on mollusks, crustaceans, and other invertebrates (Rainboth, 1996), and these phyla appeared to contain various TTX-bearing organisms (Noguchi and Arakawa, 2008).…”
Section: Why Are Toxic Puffers Having Such a Harmless Toxin?mentioning
confidence: 99%